2006
DOI: 10.1177/0013916505278458
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Environmental Values and Attitudes Between Chinese in Canada and Anglo-Canadians

Abstract: This study examines similarities and differences in environmental values and attitudes between two cultural groups—Chinese in Canada and Anglo-Canadians. The results indicate that Chinese are more supportive of social-altruistic values than are Anglo-Canadians. However, the two groups are not significantly different in biospheric values. Moreover, both groups are significantly different in two of four new environmental paradigm (NEP) subscales— limits to growth and antianthropocentrism—whereas their attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 40 publications
5
86
0
Order By: Relevance
“…3) Managers' age was included as the era in which one is brought up is arguably central to shaping environmental values, attitude and behaviours (Fryxell and Lo, 2003;Rivera and de Leon, 2005). 4) Gender was also controlled because previous research suggest that females are more likely to endorse the NEP than males (Deng et al, 2006;Egri and Herman, 2000;Snelgar, 2006). 5) The academic major was included given its obvious relationship to strategic environmental behaviour (Ewert and Baker, 2001;Rivera and de Leon, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…3) Managers' age was included as the era in which one is brought up is arguably central to shaping environmental values, attitude and behaviours (Fryxell and Lo, 2003;Rivera and de Leon, 2005). 4) Gender was also controlled because previous research suggest that females are more likely to endorse the NEP than males (Deng et al, 2006;Egri and Herman, 2000;Snelgar, 2006). 5) The academic major was included given its obvious relationship to strategic environmental behaviour (Ewert and Baker, 2001;Rivera and de Leon, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Enterprise characteristics include issues that previous studies have shown to impact on ability and willingness to engage in CSR. Management variables are gender (Deng, Walker, & Swinnerton, 2006;Egri & Herman, 2000), age (Fryxell & Lo, 2003;Rivera & de Leon, 2005) and educational level (Ewert & Baker, 2001;Rivera & de Leon, 2005). Enterprise variables are establishment antiquity (Shrivastava, 1995b), affiliation of the company to a brand or chain (Alvarez Gil et al, 2001;Ayuso, 2006;Bohdanowicz, 2006), family-ownership (Getz & Petersen, 2005;Tzschentke et al, 2008b), category (Alvarez Gil et al, 2001;Rivera, 2002) and size (Aragón-Correa et al, 2008;González-Benito & González-Benito, 2006a;Henriques & Sadorsky, 1999;Stabler, 1997).…”
Section: Instrument Designmentioning
confidence: 99%
“…The studies presented thus far provide evidence that that enterprises' characteristics and management variables have a significant impact on the ability and willingness to engage in CSR. Management variables included in the study are gender (Deng et al 2006), age (Rivera and De Leon 2005), years of experience (Kukanja, 2015), and educational level (Rivera and De Leon 2005). The selected enterprise variables are ownership structure (Getz and Petersen 2005;Tzschentke et al 2008b), category -type of the restaurant facility (Rivera 2002), and size (Aragón-Correa et al 2008;González-Benito and González-Benito 2006).…”
Section: Instrument Designmentioning
confidence: 99%